2016
DOI: 10.1007/s10658-016-0991-x
|View full text |Cite
|
Sign up to set email alerts
|

Chinese cabbage (Brassica rapa ssp. pekinensis) – a valuable source of resistance to clubroot (Plasmodiophora brassicae)

Abstract: Clubroot, caused by the protozoan parasite Plasmodiophora brassicae Woronin, is one of the most damaging diseases of Brassica napus worldwide. Resistant plant material is valuable for cultivation in all areas of high incidence of the disease and intensive growth of oilseed rape. We have evaluated clubroot resistance, plant morphology and seed quality in 15 lines of an F 4 generation and selected six lines of F 5 generation of interspecific hybrids obtained from a cross between a male sterile line of B. napus '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Uppercase letters denote the genomic origin of tagged chromosomes; Arabic numerals refer to the nomenclature of rDNA-bearing chromosomes; *Represents chromosomes A5, A6, and A9; white lines with intervals indicating recombination breakpoints. Scale bars 5 μm synthetic B. napus lines (Książczyk et al 2011;Niemann et al 2017;.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Uppercase letters denote the genomic origin of tagged chromosomes; Arabic numerals refer to the nomenclature of rDNA-bearing chromosomes; *Represents chromosomes A5, A6, and A9; white lines with intervals indicating recombination breakpoints. Scale bars 5 μm synthetic B. napus lines (Książczyk et al 2011;Niemann et al 2017;.…”
Section: Discussionmentioning
confidence: 99%
“…Using rDNA-FISH mapping combined with the C-genome-specific BAC probe, it is possible to recognize chromosome pairs: A1 (bearing 5S and 35S rDNA in opposite arms), A3 (bearing 35S rDNA (NOR) and 5S rDNA), A10 and C4 (bearing 5S rDNA), C7 (35S rDNA) and C8 (35S rDNA (NOR)) (Hasterok et al 2006 ; Xiong and Pires 2011 ). Additionally, this approach can reveal chromosome rearrangements between the A and C genomes in RS lines of Brassica (Szadkowski et al 2010 ; Książczyk et al 2011 ; Xiong et al 2011 ; Niemann et al 2017 ). Many studies have demonstrated genetic changes caused by homoeologous recombination between ancestral genomes (Parkin et al 1995 ; Udall et al 2005 ; Xiong et al 2011 ; Niemann et al 2017 ), which can contribute to the formation of new gene combinations and can also destabilize the karyotype (Gaeta and Pires 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to obtain interspecific hybrids with genetic pest resistance, paternal forms harbouring high level of resistance to B. brassicae and D. radicum were selected according to the literature data. All interspecific cross-derived lines were sister-pollinated (five plants were enclosed in one paper bag during flowering) for four generations in order to stabilize the fertility [25]. Morphotypes of plants of the F 5 -F 7 generations were compared with the parental lines, as described by Wojciechowski [26].…”
Section: Plant Materialsmentioning
confidence: 99%